Legal obstacles in Shari’ah corporate governance of Islamic financial institutions in Malaysia - Muneeza, Aishath; Hassan, Rusni (King AbdulAziz University, Kingdom Of Saudi Arabia, 2011)
This paper was sent to be published in the Journal of King Abdulaziz University for Islamic Economics. Also, it was presented in different title(1) in the Asia-Pacific Business Research Conference in Malysia, February 2011. The researchers highlighted the significant role of the Shari’ah corporate governance in the effectiveness and stability of Islamic financial Institutions in Malaysia. They outline the roles of corporate governance (in both conventional and Islamic corporation) through which it can be directed, administered and controlled. However, they argue that Shari’ah cooperate governance has different perspective and methodology. The Shari’ah cooperate governance primary is based on the tenet of Islam as the primary law and then on other positive laws, such as laws regulating the interest of the directors and the stakeholders. They described the structure of shari’ah corporate governance in Malaysia in order to emphasize and underscore some legal obstacles in the Shari’ah corporate governance and suggest some practical solutions to reform absence in the law.